(3JSgjd GdgOGjI hJMUjd GdcaGjIs - (3GHf GdfbjH , CMeO Hf dDdD Hf YHO Gddg GdQhej, TgGH GdOjf CHh GdYHGS,J (B769 (3g` s
(3ChdgG (B:s
(3jHOC HHGH bJd GdeQJO s
(3BNQgG (B:s
(3hQhi Yfg bhe Cfg jOaY GdfUa ddeYQha hjhba GdfUa hgPG eG ChQOg GdeGhQOi JaQjZkG Ydi hLg Gdhba hGddg CYde Je GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B200 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B55s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B289s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs